Piil Pesenggiri; Local Living Law between Enforcing and Diminishing Fiqh al-munÄkaá¸¥Ät - Wahyu Abdul Jafar; Abdel Salam Atwa Ali Al Fandi; Muntaser Ahmad Alqudah; Fauzan; Ahmad Alsharu (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2026)
This study aims to analyze how a local living law intervenes with fiqh al-munÄkaá¸¥Ät while turning it into a living practice, either in enforcing or diminishing the ideal concept of the latter. Piil Pesenggiri, a form of local wisdom within the Lampung community, shapes and structures how local Muslim practice their religion in term of wedding and marriage. However, its position aligning with fiqh al-munÄkaá¸¥Ät in solving the daily family problem of local Muslim was not clear enough. This study employs a socio-legal approach using qualitative methods. Data were collected through fieldwork, in-depth interviews with purposively selected informants, customary leaders, religious figures, and married couples across Central Lampung, South Lampung, and Pringsewu. The data were analyzed using the living law framework, specifically how Piil Pesenggiri as a normative â€˜inner orderâ€™ negotiates with formal fiqh doctrines, which reconstruct the daily practice of Islamic family law. The results show that when it comes to planning weddings and leading a married life, Piil Pesenggiri either upholds or downplays Islamic rule. The way Lampung people implement Islamic law in their familiesâ€”from the idea of qiwÄmah, or family division of labour, to family conflict resolution, to a number of wedding provisionsâ€”makes this negotiation very clear.